The Compositional and nutritional inventory of naturally mutant strain Auricularia cornea var. Li. edible mushroom from China - Roy, Rebecca (Progress in Nutrition, 2020)
Auricularia cornea var. Li. is a natural mutation strain of A. cornea which has been preferred byconsumers for its white colour, good taste with their pharmacological properties. Even though there are manyreports about the cultivation technologies, to the best of our knowledge, very few studies have been performedon nutritional compositions of white species of Auricularia. Therefore, this study aimed at determining thenutritional compositions of A. cornea var. Li..Eighty percent of sawdust, 18% of wheat bran and 2% of limewere used as cultivation substrate. Results were obtained by the mean ± S.E of three independent determinationsbased on the dry weight. Total dietary fiber was the dominant compound (78.94 g/100g), followedby protein (8.68 g/100g), carbohydrates (6.31 g/100g), ash (2.43 g/100g) and fat (0.91 g/100g). Potassium(1121.66 mg/100g) was the most abundant mineral, followed by magnesium (143.23 mg/100g), calcium(108.97 mg/100g) and sodium (29.22 mg/100g) in tested samples. A. cornea var. Li. has been found to containall the essential amino acids. Glutamic acid was recorded more than 13% of the total detected aminoacid content and linoleic acid was recorded more than 43% of total detected fatty acid content in this study.Although this mushroom desired for its color and flavor, it has found to be a good source of total dietary fibers,proteins, trace functional minerals, and low fat content, making it an ideal component in healthy diets.